The distribution of elephants in northeastern Ghana and northern Togo - Kotchikpa Okoumassou; Richard Barnes; Moses Sam (Pachyderm)
Reviews the preliminary study on the status of elephants in northeastern Ghana and northern Togo undertaken in April-June 1996. Assesses the recent history and present distribution of elephants including a major change in elephant distribution on both sides of the border in 1990-92, and an increase in crop raiding in the Red Volta Valley in Ghana. The elephant migration corrider between the two countries, which is important to survival, is under threat.